Risk factors for and adequacy of symptom control among children with acute asthma presenting to the emergency department Hospital USM - Termizi, Nur Syahida Mohd (2006)
Objective : To determine the adequacy of asthma control among children with astluna presenting to Emergency Department Hospital USM and to identify the risk factors for frequent visits to Emergency Department for acute asthma and the risk factors for poorly controlled asthma. Method : This is a cross sectional study, of 260 children between 5 to 12 years old who presented to the Emergency Department (ED) ~or acute astluna between September 2003 until May 2005 who requiring nebulised p2 agonist an•.d were enrolled in this study . Parents who consented for the children were interviewed in the ED, pediatric clinic or pediatric ward depending on the availability of the investigator. All information including the demographic data, asthma history, medication history and risk factors for frequent presentation at the Emergency Department and for poorly controlled asthma were listed using a standard Proforma and entered into a computer database. Result : Almost one third (27 .2%, 711260) of the children reported daytime astluna symptoms more than one per week in the previous 4 weeks. Thirty percent (30.4%, 79/260) and 22.7% (59/260) of the children reported nocturnal cough and nocturnal wheeze more than twice per month during the previous one month, respectively. Inhaled P2 agonist was used at least once per week in 34.9% (66/189) of the children during the last one month. Overall, 15.4% (40/260) of the children required hospital admission in the previous one year and 2.5% ( 1/40) of them had more than one admission. Single emergency department visit was reported in 26.2% (68/260) of children and 73.9% (192/260) required at least one revisit to ED for the last one year. About half (50.9%, 114/224)) of the children had school absenteeism at least one day in the previous one year. About one third of the children who reported having well controlled asthma were actually having persistent asthma according to the GINA guideline classification. The risk factors for frequent visit to ED were frequent use of P2 agonist bronchodilator (OR=l6.76; CI 95% 6.56-42.83), family history of eczema (OR=2.67; CI 95% 1.28-5.61), family history of asthma (OR=l.94; CI 95% 0.98-3.84) and poor compliance to treatment (OR=2.56; CI 95% 1.37-4.77). The risk factors for poorly controlled asthma were family history of asthma (OR=2.57; CI 95% 1.34-4.94), family history of allergic rhinitis (OR=2.05; CI 95% 1 .03 -~.08) and presence of allergic rhinitis (OR=2.78; CI 95% 1.32-5.82). Conclusion : The children who present with asthma symptoms to the ED at HUSM are overall not well controlled. Many of them still are disturbed by day or nocturnal symptoms. The perception of asthma control differs between the parents and GINA guideline. Several factors for frequent ED visits were identified such as poor compliance to treatment, frequent use of p2 agonist bronchodilator, fan1ily history of asthma and eczema. Presence of allergic rhinitis is also a risk factor for poorly controlled asthma along with family history of asthma and allergic rhinitis.